Advances in Atomic Force Microscopy: Weakly Perturbative Imaging of the Interfacial Water - Cao, Duanyun; Song, Yizhi; Peng, Jinbo; Ma, Runze; Guo, Jing; Chen, Ji; Li, Xinzheng; Jiang, Ying; Wang, Enge; Xu, Limei (Frontiers in Chemistry, 2019)
The structure and dynamics of interfacial water, determined by the water-interface interactions, are important for a wide range of applied fields and natural processes, such as water diffusion (Kim et al. 2013), electrochemistry (Markovic 2013), heterogeneous catalysis (Over et al. 2000), and lubrication(Zilibotti, Corni, and Righi 2013). The precise understanding of water-interface interactions largely relies on the development of atomic-scale experimental techniques (Guo et al. 2014) and computational methods (Hapala, Temirov, et al. 2014). Scanning probe microscopy has been extensively applied to probe interfacial water in many interdisciplinary fields (Ichii et al. 2012; Shiotari and Sugimoto 2017; Peng, Cao, et al. 2018). In this perspective, we review the recent progress in the noncontact atomic force microscopy (nc-AFM) imaging and AFM simulation techniques and discuss how the newly developed techniques are applied to study the properties of interfacial water. The nc-AFM with the quadrupole-like CO-terminated tip can achieve ultrahigh-resolution imaging of the interfacial water on different surfaces, trace the reconstruction of H-bonding network and determine the intrinsic structures of the weakly bonded water clusters and even their metastable states. In the end, we present an outlook on the directions of future AFM studies of interfacial water as well as the challenges faced by this field.